EVALUASI FISIK DAN NUTRISI PAKAN BENTUK MASH, PELLET DAN WAFER BERBAHAN LEGUME INDIGOFERA - Harahap, Anwar Efendi; Adelina, T; Ramadhan, F (Jurnal Peternakan Nusantara, 2024)
The problem faced in the livestock business is the insufficiency of feed raw materials both in quality and quantity, even though there is a supply of feed using indigofera legumes with physical innovations in the form of mash, pellet and wafer feed. This research aims to test the quality of feed made from indigofera legumes in various forms of mash, pellets and wafers. This study used a completely randomized plan with 3 treatments and 6 replications. The treatment S0 = Mash  feed composition of 50% indigofera legumes + 50% corn bran + 5% binding molasses; S1= pellets composition of 50% indigofera beans + 50% corn bran + 5% molasses; S2 = Wafer composition of 50% indigofera legumes + 50% corn bran + 5% molasses. The results showed that the pellet treatment produced higher specific gravity, pile density and compaction density values ​​(P<0.05) than the mash treatment, furthermore the wafer treatment was superior in producing dry matter and crude protein compared to the mash and pellet treatments. The research conclusion is that wafer feed is superior in producing crude protein and dry matter values.